2022
DOI: 10.26499/surbet.v17i1.317
|View full text |Cite
|
Sign up to set email alerts
|

Hegemoni dalam Naskah Drama 5 Babak Atas Nama Cinta Karya Agus R. Sarjono: Perspektif Antonio Gramsci

Abstract: Hegemony in Five Act Drama Scripts Atas Nama Cinta by Agus R. Sarjono: Antonio Gramsci' PerspectiveThis research discusses the issue of state issues in the drama script Atas Nama Cinta by Agus R. Sarjono. The phenomenon of sarcasm or criticism of the social problems that occurred in Indonesia has implied output written in the drama script is relevant to be studied using the sociology of literature. The concept of Antonio Gramsci's Hegemony includes culture, hegemony, common sense, intellectuals, and state in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The result showed that there is a group of people that hegemonize others. Moreover, the unequal ideology of education made them have different ways to resolve their problems (Efendi et al, 2022). Naufina analyzed patriarchal hegemony portrayed in a dystopian world where young girls are hegemonized to fulfill patriarchal interests written by Louise O' Neill, Only Ever Yours.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that there is a group of people that hegemonize others. Moreover, the unequal ideology of education made them have different ways to resolve their problems (Efendi et al, 2022). Naufina analyzed patriarchal hegemony portrayed in a dystopian world where young girls are hegemonized to fulfill patriarchal interests written by Louise O' Neill, Only Ever Yours.…”
Section: Introductionmentioning
confidence: 99%